CYP2C19 genotype and platelet aggregation test-guided dual antiplatelet therapy after off-pump coronary artery bypass grafting: A retrospective cohort study - Yao, Haoyi; Qin, Kaijie; Liu, Yun; Yang, Yi; Zhu, Jiaxi; Chen, Anqing; Wang, Zhe; Ye, Xiaofeng; Zhou, Mi; Li, Haiqing; Qiu, Jiapei; Zhao, Qiang; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Dual antiplatelet therapy (DAPT) is recommended for patients underwent off-pump coronary artery bypass graft surgery (OPCAB). Clopidogrel was less effective among patients those who with loss-of-function (LoF) of CYP2C19 alleles, while ticagrelor has direct effects on P2Y12 receptor. Whether a CYP2C19 genotype plus platelet aggregation test (PAgT)-guided DAPT strategy after CABG could improve the clinical outcome remains uncertain. Methods: From August 2019 to December 2020, a consecutive 1134 patients underwent OPCAB in our site received either a traditional DAPT group (aspirin 100mg qd + clopidogrel 75mg qd) or an individual DAPT group (aspirin 100mg qd + clopidogrel 75mg qd if CYP2C19 extensive metabolizer; aspirin 100mg qd + ticagrelor 90mg bid if CYP2C19 poor metabolizer; and aspirin 100mg qd + clopidogrel 75mg qd if CYP2C19 moderate metabolizer and normal response in PAgT, or aspirin 100mg qd + ticagrelor 90mg bid if CYP2C19 moderate metabolizer and low response in PAgT) for 1 year after surgery. The primary outcome was MACE (composite of CV death, MI, and stroke). The safety outcome was TIMI-criteria major bleedings. Results: A total of 382(33.7%) and 752(66.3%) patients received the traditional or individual DAPT strategy, respectively. Compared with the traditional DAPT group, the risk of MACE in the individual DAPT group was significantly lower (5.5% vs 9.2%, HR 0.583; 95% CI, 0.371 to 0.915; P=0.019), this mainly due to the decreased risk of MI (1.7% vs 4.2%, HR 0.407; 95% CI, 0.196 to 0.846; P=0.016). The risk of major bleeding events between groups was similar (5.3% vs 6.0%, RR 0.883; 95% CI, 0.537 to 1.453; P=0.626). Conclusion: For patients underwent OPCAB need for DAPT, a CYP2C19 genotype plus PAgT-guided individual strategy was associated with a lower risk of MACE and similar risk of major bleeding.